Barriers to Social Sustainability in Residential Building Construction in Afghanistan - Mohammadi, Mohammad Qasim; Rohman, Mohammad A. (Journal of Civil Engineering, 2025)
Although socially sustainable buildings are becoming increasingly popular worldwide, past studies indicate that when policymakers support sustainable building development, the social dimension is often given less attention or is entirely disregarded. There is not much research that focus on the challenges of socially sustainable buildings in Afghanistan. This research investigated the factors that hinder implementation of social sustainability in residential building construction. The study collected data from construction professionals and employed Exploratory Factor Analysis (EFA) and Varimax for analysis.  The findings are critically analysed and discussed. The results indicate that there are six underlying factors for the barriers to socially sustainable building construction in this context. Among these barriers, lack of urban planning, awareness, and economic incentives are rated as the greatest impediments to social sustainability in residential buildings. The primary goal of this study is to reduce the barriers’ dimensionality to make it easier for practitioners to overcome challenges. Moreover, to inform decision-making in the industry and encourage the adoption of more socially sustainable construction practices.